2018
DOI: 10.1007/s12010-018-2851-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Production of Phenolic Compounds in Compact Callus Aggregate Suspension Cultures of Rhodiola imbricata Edgew.

Abstract: Rhodiola imbricata is a rare medicinal plant of the trans-Himalayan region of Ladakh. It is used for the treatment of numerous health ailments. Compact callus aggregate (CCA) suspension cultures of Rhodiola imbricata were established to counter extinction threats and for production of therapeutically valuable phenolic compounds to meet their increasing industrial demands. The present study also investigated the effect of jasmonic acid (JA) on production of phenolic compounds and bioactivities in CCA suspension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 100 publications
0
6
0
1
Order By: Relevance
“…To obtain callus cultures of Rhodiola species, cytokinin BAP is most often employed in combination with various auxins. Compact callus aggregate suspension cultures of Rhodiola imbricata are obtained on the MS medium supplemented with 3 mg/L NAA and 3 mg/L BAP [ 28 ]. Rhodiola quadrifida (Pall.)…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To obtain callus cultures of Rhodiola species, cytokinin BAP is most often employed in combination with various auxins. Compact callus aggregate suspension cultures of Rhodiola imbricata are obtained on the MS medium supplemented with 3 mg/L NAA and 3 mg/L BAP [ 28 ]. Rhodiola quadrifida (Pall.)…”
Section: Discussionmentioning
confidence: 99%
“…We showed that when callus cultures are exposed to an elicitor, phenolic compounds emerge that are absent in the sample without treatment; their retention times are 13.6, 30.0, 33.3, and 46.0 min. The effectiveness of MJ as an elicitor has been demonstrated for many in vitro cultures, including those of Rhodiola species [ 28 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. For example, for Rhodiola it is reported that the levels of bioactive compounds increase with MJ supplementation in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations